Anti-plagiarism Literacy through the Utilization of Digital Technology-Based Reference Management Applications among Lecturers at Al-Islam Polytechnic, Bandung City: Literasi Antiplagiarisme melalui Pemanfaatan Aplikasi Pengelola Referensi Berbasis Teknologi Digital di Kalangan Dosen Politeknik Al-Islam Kota Bandung - Sukaemi, Linda Handayani; Sulistyaningtyas, Tri; Waskita, Dana; Suryani, Yani; Muchsonah; Gunta Pertiwi, Untari; Kamila, Sira (Universitas Lancang Kuning, 2025)
In the context of scientific writing, the use of references or source material is of significant importance in ensuring the scientific rigour and quality of the paper in question. It is imperative that any quality scientific work make use of credible and reputable references, whether at the national or international level. It is not sufficient to simply use reputable references; the ability to manage reference sources is also required when presenting a literature review and research methods. Effective management of reference sources ensures that scientific work is free from plagiarism. The objective of this activity is to equip lecturers with the skills to utilise a reference manager, thereby streamlining the citation process and guaranteeing the inclusion of all referenced material in the bibliography. This programme constitutes the second activity in the series of training sessions on the writing of scientific papers, which were conducted by the Literacy, Media, and Culture Group in 2022. The training will provide lecturers with an understanding of the principles of writing quality scientific papers, as well as practical tips and techniques for implementing these principles in their own work. This activity aims to equip lecturers with the skills to avoid plagiarism and adapt their ideas to the format or style of the intended journal, ensuring that their work is written in standardised academic language. Following this training, lecturers should be able to produce scientific journals that meet the standards required for publication in reputable national and international journals.